Implementation of the Indonesia Sustainable Palm Oil (ISPO) Policy on Oil Palm Plantations in West Kalimantan - Suratiningsih, Dewi; Hardilina, Hardilina; Anugrah, Akhmad Rifky Setya; Safira, Safira; Puspita, Dea (Jurnal Hubungan Internasional, 2024)
When it comes to palm oil, Indonesia dominates the global market. However, the European Union Parliament’s Renewable Energy Directive (RED) policy created roadblocks for the Indonesian palm oil industry’s European exports because the product did not adhere to sustainability principles. In 2009, Indonesia adopted the Indonesian Sustainable Palm Oil (ISPO) policy in response to the European Union’s RED. This policy aims to promote sustainable practices on oil palm plantations. The government of Indonesia is likewise working to increase ISPO’s visibility abroad. Regarding Indonesian provinces, West Kalimantan has the third-largest area dedicated to oil palm plantations. However, only a few palm oil producers have obtained ISPO certification. This study aims to determine why the ISPO policy was ineffective in West Kalimantan by examining the challenges of enforcing the policy through the lenses of sustainable development and policy implementation. A descriptive qualitative method was applied, with data gathered through in-depth interviews, observation, and documentation. Non-specific policy substance, information restrictions, governmental policies not supporting implementation, and probable distribution problems among the parties engaged in execution were only a few factors this study cited impeding the ISPO policy implementation in West Kalimantan.